Composite conductive paste transfer printing film, photovoltaic electrode grid line preparation method and photovoltaic cell

Through the composite conductive paste transfer film and nanoimprinting process, combined with the use of copper paste and silver paste, the problems of high cost and single process in traditional technology are solved, and the preparation and production efficiency of high-resolution electrode patterns are achieved. Improvement reduces production costs, and the process is simple, environmentally friendly and sustainable.

CN119217879APending Publication Date: 2024-12-31BEIJING ZENITHNANO TECH CO LTD +1

Patent Information

Application Number
CN202411372710.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Although the traditional all-silver paste conductive path has good conductivity, the cost of silver paste is high, resulting in excessive production costs. The existing transfer film preparation process is relatively single, which cannot meet the needs of high resolution and efficient production.

Method used

Using the preparation method of composite conductive paste transfer film, the PVA film with a preset thickness and imprinting is used as the base material to fill and imprint the conductive paste to form a composite layer, and combine with the nano-imprinting process to achieve a high-resolution electrode pattern. The production cost is reduced by using the combination of copper paste and silver paste.

Benefits of technology

The preparation of high-resolution electrode patterns is realized, which reduces production costs and improves production efficiency, solves the problems of high cost and single process in traditional technology, and is simple in the process, environmentally friendly and sustainable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119217879A_ABST
    Figure CN119217879A_ABST
Patent Text Reader

Abstract

The invention discloses a composite conductive paste transfer film, a photovoltaic electrode grid line preparation method and a photovoltaic cell, and relates to the technical field of photovoltaic cells. According to the preparation method of the composite conductive slurry transfer printing film, high-precision impressing forming, transfer printing, dissolving and other technologies are adopted for a PVA film, and composite conductive slurry is adopted, so that precise electrode design is achieved on a crystal silicon wafer. The high-precision impressing technology and the transfer printing technology are applied to preparation of the photovoltaic electrode grid line, and the precision and the resolution ratio of the electrode grid line can be greatly improved. Compared with a traditional single silver paste grid line, the use amount of silver paste can be reduced and the industrial cost can be reduced on the basis of achieving higher photoelectric conversion efficiency by using the composite conductive paste. The PVA film with proper thickness and hardness is directly used as a substrate to complete transfer printing, a conventional complex structure of a transfer printing substrate film and a water-soluble polymer coating is replaced, and the problems that the silicon wafer is damaged and the grid line structure is influenced due to the fact that the subsequent substrate cannot be easily separated from the crystal silicon wafer can also be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic cells, and in particular to a composite conductive slurry transfer film, a photovoltaic electrode grid line preparation method, and a photovoltaic cell. Background Art

[0002] With the advancement of the national carbon peak and carbon neutrality goals, the work of building a new power system with new energy as the main body is being accelerated, and the status of the photovoltaic industry has been significantly improved; solar cells are the core components of photovoltaic systems, and industrial production based on single-crystal silicon photovoltaic cells occupies an important position, accounting for more than 90% of the total solar cell output; electrode grid lines are key components of batteries, and they have a great impact on the performance of solar cells; the material of electrode grid lines is mainly materials with good conductive properties, and silver paste is one of the most widely used electrode grid line materials at present, with excellent conductive properties and chemical stability, and is suitable for the preparation of photovoltaic cells; optimizing the preparation process of silver paste grid lines can effectively improve the photoelectric conversion efficiency of solar cells.

[0003] Silver paste gridline printing technology for photovoltaic cells is one of the key production processes, which is mainly used to form electrodes on silicon wafers to collect current generated by the photovoltaic effect. Common electrode gridline printing technologies mainly include: screen printing, inkjet printing, offset printing and flexible printing. Screen printing technology is the most commonly used. This technology prints silver paste on the surface of photovoltaic cells through a screen to form an electrode pattern, thereby realizing the collection and conduction of electrical energy.

[0004] Although screen printing technology is more commonly used, it still has some shortcomings compared to transfer silver paste technology; for example: transfer silver paste technology has the advantages of higher resolution, more stable finished product quality, higher production efficiency, wider applicability and greater durability.

[0005] However, although the traditional all-silver paste conductive path has good conductivity, the cost of silver paste is more expensive than copper paste, resulting in excessively high production costs; and the existing transfer film preparation process is relatively simple. There is currently no effective solution to the above problems. Summary of the invention

[0006] Purpose of the invention: To provide a composite conductive paste transfer film and a method for preparing a photovoltaic electrode grid line and a photovoltaic cell, so as to solve at least one of the problems existing in the above-mentioned prior art.

[0007] Technical solution: A method for preparing a composite conductive paste transfer film, comprising the following steps:

[0008] S11, providing a first substrate having a preset thickness and having an electrode pattern groove formed by embossing;

[0009] S12, coating the first conductive paste on the embossing side of the first substrate so as to at least fill the groove, and removing the excess first conductive paste on the surface of the first substrate so that the groove and the surface of the first conductive paste are located on the same plane;

[0010] S13, using a first mold to emboss the first conductive paste in the groove into a preset shape and leaving a gap, and removing the overflowed first conductive paste after embossing;

[0011] S14, coating the second conductive paste in the preset shape, compounding the second conductive paste on the first conductive paste, and removing the excess second conductive paste on the surface of the first substrate to complete the preparation of the transfer film.

[0012] Preferably, before S11, providing a first substrate having a preset thickness and embossing a first substrate having an electrode pattern groove, the method further includes:

[0013] PVA films with a thickness of 30-125um were prepared by electrospinning or flat coating.

[0014] Preferably, the PVA film has a width of 200-800 um, an elongation at break of 20-60%, a tensile strength of 5-20 MPa, and a Shore A hardness of greater than 70HS.

[0015] Preferably, S11, providing a first substrate having a preset thickness and having an electrode pattern groove formed by embossing, comprising:

[0016] The prepared PVA film is placed in the second mold by a precision hot press and hot embossing is performed in the temperature range of 150-200°C to form a micrometer-scale or even nanometer-scale electrode groove structure on the surface of the PVA film.

[0017] Preferably, the first mold and the second mold are one of a single crystal silicon substrate, a polycrystalline silicon substrate, a copper substrate, a nickel substrate, a copper-nickel alloy substrate, a nickel-iron alloy substrate, an iron-aluminum alloy substrate or an aluminum alloy substrate.

[0018] Preferably, the convex portion of the second mold is complementary in shape to the concave portion;

[0019] Wherein, the shape of the mold is one of an isosceles triangle, an isosceles trapezoid, an ellipse, a hexagon, a right-angled trapezoid or a rectangle.

[0020] Preferably, S12, coating a first conductive paste that can at least fill the groove on the embossing side of the first substrate, and removing excess first conductive paste on the surface of the first substrate so that the groove and the surface of the first conductive paste are located on the same plane, comprising:

[0021] The first conductive paste is evenly applied on the heat-pressed PVA film by a flat coating method, so that the first conductive paste completely fills the groove, and the excess first conductive paste is scraped off to ensure that the first conductive paste is completely filled and evenly distributed without deformation.

[0022] Preferably, S13, using a first mold to emboss the first conductive paste in the groove into a preset shape and leaving a gap, and removing the overflowed first conductive paste after embossing, comprises:

[0023] A groove pattern with a height of 2-5 um, a width of 5 um and a reserved gap is pressed out using the first mold according to preset requirements, and the first conductive paste is dried at 100-200°C.

[0024] Preferably, S14, coating a second conductive paste in a preset shape, compounding the second conductive paste on the first conductive paste, and removing excess second conductive paste on the surface of the first substrate, comprises:

[0025] The coated second conductive paste is closely contacted with the formed first conductive paste to form a firm composite layer;

[0026] By heating or applying pressure, the conductive pastes are fused together to ensure that there are no gaps in the composite layer and to form a continuous conductive path; wherein the heating temperature is 50-80°C and the duration is 5-10 minutes.

[0027] Preferably, S14, coating the second conductive paste in a preset shape, compounding the second conductive paste on the first conductive paste, and removing excess second conductive paste on the surface of the first substrate, further comprises:

[0028] After removing the excess slurry, the conductive slurry needs to be initially dried at 80-100°C for 10-20 minutes to evaporate part of the solvent in the slurry and ensure that the slurry is initially solidified;

[0029] In order to completely cure the conductive paste, high-temperature curing treatment is performed again at a temperature of 150-200°C and a curing time of 30-60 minutes. During this process, the internal structure of the conductive paste will be cross-linked and sintered, the conductive performance will be improved, and a stable electrode grid line will be formed.

[0030] Preferably, the first conductive paste is one of copper paste, chromium paste, tin paste, indium paste, nickel paste, titanium paste and tantalum paste, and the second conductive paste is silver paste;

[0031] Wherein, the silver paste comprises a binder, and the binder is a phenolic resin or an epoxy resin.

[0032] Preferably, the first substrate is made of a water-soluble polymer material, and the water-soluble polymer material is one of polyvinyl alcohol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, polyvinyl alcohol-polyacrylonitrile, polyvinyl pyrrolidone or polyethylene glycol.

[0033] Preferably, the longitudinal cross-section of the groove of the electrode pattern is in the shape of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle or a polygon.

[0034] In order to achieve the above objective, according to another aspect of the present application, a method for preparing a photovoltaic electrode grid line is also provided.

[0035] The photovoltaic electrode grid line preparation method according to the present application comprises the following steps:

[0036] S1. Providing a transfer film prepared by a composite conductive paste transfer film preparation method;

[0037] S2, providing a second substrate, laminating the side of the first substrate having the conductive paste to the second substrate, and transferring the first conductive paste and the second conductive paste to the substrate by a embossing method with preset process parameters; wherein the embossing process parameters are: pressure of 5-20MPa, temperature of 80-180°C and time of 1-10min;

[0038] S3, removing the first substrate so that the first conductive paste and the second conductive paste remain on the second substrate;

[0039] S4, sintering the first conductive paste and the second conductive paste on the second substrate to form photovoltaic composite paste electrode grid lines with a preset aspect ratio.

[0040] Preferably, S2, providing a second substrate, and laminating the first substrate with the side of the conductive paste on the second substrate, comprising:

[0041] The first conductive paste and the second conductive paste are hot-pressed and transferred to the second substrate by applying uniform pressure and heating and drying. At the same time, the first conductive paste and the second conductive paste are heated and dried so that they are tightly attached to the surface of the substrate without deformation; wherein the second substrate is one of a single crystal silicon substrate, a polycrystalline silicon substrate, a perovskite substrate, a glass substrate, and a plastic substrate.

[0042] Preferably, S3, removing the first substrate so that the first conductive paste and the second conductive paste remain on the second substrate, comprises:

[0043] The transferred silicon wafer is placed in 25-75°C water for cleaning, so that the PVA film dissolves and falls off, leaving the successfully transferred composite slurry pattern to form the basic structure of the photovoltaic electrode grid line.

[0044] Preferably, S4, sintering the first conductive paste and the second conductive paste on the second substrate to form a photovoltaic composite paste electrode grid line with a preset aspect ratio, comprising:

[0045] The silicon wafer after transferring the first conductive paste and the second conductive paste is placed in a high-temperature furnace to sinter the composite paste; the sintering temperature is 500-800°C to ensure that the silver paste is completely sintered and forms a tight connection with the silicon wafer to generate high-precision photovoltaic electrode grid lines with a preset aspect ratio.

[0046] In order to achieve the above objective, according to another aspect of the present application, a photovoltaic cell is provided.

[0047] The photovoltaic cell according to the present application is characterized by comprising the prepared photovoltaic electrode grid lines.

[0048] Preferably, the method comprises: a second substrate layer;

[0049] A second conductive paste layer is disposed on the second substrate layer at intervals along a length direction of the second substrate layer; and

[0050] a first conductive paste layer connected to the second conductive paste layer in a thickness direction perpendicular to the second substrate layer;

[0051] The longitudinal cross-section of the first conductive paste layer is one of an isosceles triangle, an isosceles trapezoid, an ellipse, a hexagon, a right-angled trapezoid or a rectangle; the longitudinal cross-section of the second conductive paste layer is an isosceles trapezoid.

[0052] Preferably, a passivation coating is provided between the first conductive paste layer and the second conductive paste layer.

[0053] Beneficial effect: In the embodiment of the present application, a preparation process of a high-resolution composite silver / copper paste transfer film based on a PVA carrier and a nanoimprint process is adopted, by providing a first substrate with a preset thickness and an electrode pattern groove formed by imprinting; a first conductive paste that can at least fill the groove is applied to the imprinting side of the first substrate, and the excess first conductive paste on the surface of the first substrate is removed so that the surface of the groove and the surface of the first conductive paste are located on the same plane; a first mold is used to imprint the first conductive paste in the groove into a preset shape and a gap is reserved, and the overflowed first conductive paste is removed after the imprinting; a second conductive paste is applied in the preset shape, the second conductive paste is compounded on the first conductive paste, and the excess second conductive paste on the surface of the first substrate is removed to complete the preparation of the transfer film, thereby achieving the purpose of composite silver / copper paste, nanoimprinting and preparing the transfer film, thereby achieving the technical effect of reducing production costs and preparing high-resolution electrode patterns, thereby solving the problem of the traditional all-silver paste conductive path, although the conductive effect is good, the cost of silver paste is more expensive than copper paste, resulting in excessively high production costs; and the technical problem that the existing transfer film preparation process is relatively single. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 It is a schematic diagram of the process of preparing the photovoltaic electrode grid line of the present invention;

[0055] Figure 2 It is a schematic flow chart of another method for preparing photovoltaic electrode grid lines of the present invention;

[0056] Figure 3 It is a schematic flow diagram of the method for preparing the composite conductive paste transfer film of the present invention;

[0057] Figure 4 is a schematic diagram of the structure of a composite conductive paste layer in the method for preparing a composite conductive paste transfer film of the present invention; and

[0058] Figure 5 It is a schematic diagram of the mold structure in the method for preparing the composite conductive paste transfer film of the present invention. DETAILED DESCRIPTION

[0059] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present application.

[0060] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequential order. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application described here. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0061] In addition, the terms "installed", "set", "provided with", "connected", "connected", and "socketed" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0062] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0063] In order to better understand this application, the following explanation is given:

[0064] At present, the screen printing technology is mature and the equipment is popular. However, the accuracy of the screen printing process is limited by the screen aperture and printing pressure, making it difficult to achieve very fine patterns and high-resolution printing. Generally, the silver paste line width is at least tens of microns. Moreover, a certain amount of waste will be generated during the screen printing process, resulting in material waste. The screen plug has a limited service life, is expensive, and has a high overall cost. In addition, screen printing is a relatively slow production process that cannot meet the needs of large-scale production, affecting production efficiency.

[0065] Therefore, it is particularly important to develop a new photovoltaic cell electrode grid line printing technology with simple process technology, low process cost and high resolution.

[0066] like Figure 1-5 As shown, the present application relates to a composite conductive paste transfer film and a method for preparing a photovoltaic electrode grid line, and a photovoltaic cell. Figure 3 As shown, the method for preparing a composite conductive paste transfer film comprises the following steps:

[0067] S11, providing a first substrate having a preset thickness and having an electrode pattern groove formed by embossing;

[0068] The desired electrode pattern can be obtained by embossing, thereby achieving the effect of improving precision and facilitating implementation. The embossing can be hot embossing.

[0069] According to an embodiment of the present invention, preferably, S11, providing a first substrate having a preset thickness and having an electrode pattern groove formed by embossing, comprises:

[0070] The prepared PVA film is placed in the second mold by a precision hot press and hot embossing is performed in a temperature range of 150-200°C, so that a micron-scale or even nano-scale electrode groove structure is formed on the surface of the PVA film;

[0071] Specifically, the above process steps include but are not limited to:

[0072] 1. Mold preparation: Clean the preset mold and ensure that there are no stains and particles on its surface to ensure the quality of embossing;

[0073] 2. Preparation of the first substrate: Prepare the first substrate and ensure that the surface is flat and clean; for example, the first substrate is PVA;

[0074] 3. Heating and embossing: Align the mold with the substrate and emboss at a set temperature; the pressure and time are controlled by the above parameters to ensure that the mold pattern is completely pressed into the substrate;

[0075] Of course, parameter control can be set according to actual usage requirements and is not limited in this application.

[0076] 4. Cooling and demolding: After the imprinting is completed, the mold and the first substrate are cooled to ensure that the material is fixed, and then the mold is carefully demolded to obtain the first substrate with the electrode pattern groove.

[0077] By adopting a hot pressing molding machine, the precision of the PVP transfer coating after hot pressing molding can be guaranteed, and the size and shape of the grid line can be reasonably designed to reduce the ohmic loss.

[0078] According to an embodiment of the present invention, preferably, the first mold and the second mold are one of a single crystal silicon substrate, a polycrystalline silicon substrate, a copper substrate, a nickel substrate, a copper-nickel alloy substrate, a nickel-iron alloy substrate, an iron-aluminum alloy substrate or an aluminum alloy substrate.

[0079] It is possible to achieve the effect of having a variety of materials to choose from, thereby achieving the effect of flexible use, and thus the effect that can be easily achieved.

[0080] It is important to know that: single crystal silicon substrate: has excellent electrical conductivity and thermal stability, and is often used in the manufacture of high-efficiency photovoltaic cells; polycrystalline silicon substrate: has relatively low cost, and has high mechanical strength and stability, and is widely used in the photovoltaic field; copper substrate: has good electrical conductivity and thermal conductivity, and is suitable for application scenarios that require fast electrical conduction; nickel substrate: has excellent corrosion resistance and mechanical strength, and is suitable for the manufacture of electrodes for long-term use; copper-nickel alloy substrate: combines the electrical conductivity of copper and the corrosion resistance of nickel, and is suitable for high-demand electrical equipment; nickel-iron alloy substrate: is magnetic and corrosion-resistant, and is often used in the manufacture of electromagnetic devices; iron-aluminum alloy substrate: is light in weight, resistant to high temperature and corrosion, and is suitable for electrode applications in aerospace and high-temperature environments; aluminum alloy substrate: is light in weight and has good thermal conductivity, and is widely used in photovoltaic cell frames and electrical conductors.

[0081] like Figure 5 As shown, according to an embodiment of the present invention, preferably, the convex portion of the second mold is complementary in shape to the concave portion;

[0082] The shape of the mold is one of an isosceles triangle, an isosceles trapezoid, an ellipse, a hexagon, a right-angled trapezoid or a rectangle. It is understandable that the shape and size of the convex portion correspond to the electrode grid line, and in actual operation, the size and shape of the electrode grid line to be transferred are controlled to reduce the ohmic loss of the electrode grid line; the longitudinal cross-sectional shape of the convex portion includes but is not limited to: one of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, and a polygon; in this embodiment, preferably, the longitudinal cross-sectional shape of the convex portion is a triangle or a trapezoid, and the longitudinal cross-sectional design of a triangle or a trapezoid helps to change the incident and refraction path of light, can better capture and guide light, can effectively reduce the reflection loss of light, so that more light is absorbed by the semiconductor material and converted into electrical energy, thereby improving the photoelectric conversion efficiency.

[0083] By designing the shapes of the convex and concave parts of the mold to be complementary structures, precise docking and embossing molding effects can be ensured during the mold molding process, thereby achieving a high-precision transfer effect and improving the quality of the electrode grid lines of the final product.

[0084] Specifically, the shape of the mold can be selected from several geometric structures including but not limited to the following: Isosceles triangle: suitable for scenarios that require concentrated force transmission, and can form a sharp and clear transfer effect at the edge of the photovoltaic electrode grid line. Isosceles trapezoid: It has a larger bottom width and a narrower top structure, which is suitable for applications that require electrode grid lines with gradient widths to ensure uniform filling during the transfer process. Oval: It can provide a smooth edge transition effect, which is suitable for electrode designs that require more uniform current distribution, reducing resistance and local stress concentration. Hexagon: It has a stable structure and good density distribution effect, and is suitable for electrode grid line designs that need to improve transfer accuracy and stability. Right-angle trapezoid: It is suitable for photovoltaic electrode designs that require uniform grid line width and neat edges to ensure the accuracy of current distribution. Rectangle: A classic and common design, suitable for the transfer of standardized photovoltaic electrode grid lines, providing the largest contact area to improve current conduction efficiency.

[0085] According to an embodiment of the present invention, preferably, the aspect ratio of the second mold shape is in the range of 1-3.

[0086] By setting the aspect ratio of the mold shape to a range of 1-3, the relationship between the height and width of the convex portion of the mold can be effectively adjusted, thereby optimizing the transfer effect of the electrode grid lines.

[0087] By setting the aspect ratio of the mold shape to a range of 1-3, the relationship between the height and width of the convex portion of the mold can be effectively adjusted, thereby optimizing the transfer effect of the electrode grid lines.

[0088] Specifically, when the aspect ratio is 1, the height and width of the mold are equal, which is suitable for electrode structures that require relatively flat gate lines and uniform thickness and width. This ensures that the electrode has good conductivity and that the silver paste can be evenly distributed during the transfer process.

[0089] In this embodiment, preferably, when the aspect ratio is close to 2, a moderate thickness and width are provided, so that the grid line has a certain height to improve the mechanical strength of the electrode, but is not too wide to maintain a fine structure. It is suitable for conventional photovoltaic electrode manufacturing and balances resistance, strength and process difficulty.

[0090] When the aspect ratio is 3, the height of the gate line is significantly greater than the width, which is suitable for more sophisticated narrow electrode designs. It can effectively reduce resistance and increase current density, but requires higher mold precision during the manufacturing process to ensure that the silver paste is fully filled in the narrow groove.

[0091] Therefore, the flexible setting of the aspect ratio range allows the geometry of the electrode grid lines to be adjusted according to different photovoltaic cell design requirements to achieve the best balance between conductivity, mechanical strength and production process.

[0092] S12, coating the first conductive paste on the embossing side of the first substrate so as to at least fill the groove, and removing the excess first conductive paste on the surface of the first substrate so that the groove and the surface of the first conductive paste are located on the same plane;

[0093] A good coating effect of the first conductive paste can be achieved, so that the first conductive paste is evenly filled and distributed in the grooves of the first substrate, thereby providing a basis and guarantee for subsequent imprinting.

[0094] According to an embodiment of the present invention, preferably, S12, coating a first conductive paste that can at least fill the groove on the embossing side of the first substrate, and removing excess first conductive paste on the surface of the first substrate so that the groove and the surface of the first conductive paste are located on the same plane, includes:

[0095] The first conductive paste is evenly applied on the first substrate that has been hot-pressed by using a flat coating method, so that the first conductive paste completely fills the groove, and the excess first conductive paste is scraped off to ensure that the first conductive paste is completely filled and evenly distributed without deformation. The first substrate is a PVA film.

[0096] Specifically, the above process steps include but are not limited to:

[0097] 1. Prepare the coating environment

[0098] 1.1 Fix the first hot-pressed substrate on the workbench of the flat-bed coater to ensure its stability and avoid movement or deformation during the coating process;

[0099] 1.2 Prepare the first conductive paste, ensure that it is evenly stirred, has no particle deposition, and has moderate viscosity; the ideal conductive paste viscosity range is usually 1000-5000cP, depending on the coating requirements.

[0100] 2. Coating process

[0101] 2.1 Uniform coating: The first conductive paste is evenly coated on the surface of the first substrate by a flat coater. The coating thickness needs to be properly controlled to ensure that the groove can be completely filled;

[0102] 2.2 Pressure control: The pressure applied during coating should be moderate to ensure that the slurry can evenly enter the groove without causing deformation of the substrate; the pressure range can be controlled between 0.1MPa-0.5MPa, and the specific value is adjusted according to the flexibility of the substrate and the shape of the groove.

[0103] 3. Scrape off excess slurry

[0104] 3.1 Scraper operation: Use a scraper to gently scrape off the excess conductive slurry on the surface of the substrate, ensuring that the conductive slurry only fills the groove area and the surface is flat without deformation or accumulation; the scraper should use moderate pressure to prevent the slurry in the groove from being scraped off; the scraper angle is recommended to be controlled at 45°-60° and operated at a steady speed to avoid damaging the substrate surface;

[0105] 3.2 Scraper material: It is recommended to use a scraper made of a material with moderate hardness, such as polytetrafluoroethylene (PTFE), polyurethane (PU) or flexible metal to avoid scratching the substrate during operation.

[0106] 4. Slurry filling inspection

[0107] 4.1 Visual inspection: Check whether the groove is completely filled with conductive paste by optical microscope or other visual inspection methods; ensure that there are no bubbles or gaps in the groove and the surface paste is evenly distributed;

[0108] 4.2 Thickness control: Check whether the thickness of the slurry after coating meets the predetermined standard. A thickness gauge or surface profiler can be used to measure the thickness of the slurry in the groove to ensure the uniformity of the conductive layer.

[0109] It should be known that one of the main components of photovoltaic silver paste is adhesive (phenolic resin, epoxy resin, etc.), whose function is to form a stable bond between the silver paste particles and between the particles and the silicon wafer.

[0110] S13, using a first mold to emboss the first conductive paste in the groove into a preset shape and leaving a gap, and removing the overflowed first conductive paste after embossing;

[0111] On the first conductive paste that has been coated and filled in the groove, embossing is performed using a first mold, which can further compact the first conductive paste to conform to a preset shape, while reserving a certain gap for subsequent process operations.

[0112] According to an embodiment of the present invention, preferably, S13, using a first mold to emboss the first conductive paste in the groove into a preset shape and leaving a gap, and removing the overflowed first conductive paste after embossing, comprises:

[0113] A groove pattern with a height of 2-5 um, a width of 5 um and a reserved gap is pressed out using the first mold according to preset requirements, and the first conductive paste is dried at 100-200°C.

[0114] Specifically, the above process steps include but are not limited to:

[0115] The first mold embossing groove: The height of the mold groove is 2-5μm and the width is 5μm. The bottom of the mold should have a high-precision micro-nano structure, and the material should be selected from cemented carbide or hardened steel to ensure durability and accuracy. The mold surface should be treated with an anti-stick coating, such as a fluoride coating, to prevent the conductive paste from adhering to the mold surface.

[0116] Apply pressure: The pressure of the stamping should be kept stable to ensure that the slurry is completely pressed into the groove. Generally, it is recommended to control the pressure at 0.1MPa-0.5MPa; too much pressure will cause excessive overflow of the slurry, and too little pressure will not completely compact the slurry.

[0117] Imprinting time: The time should be determined according to the fluidity of the conductive paste and the imprinting pressure; the imprinting time is 30 seconds to 2 minutes. Too short a time may result in incomplete imprinting, and too long a time may cause deformation of the substrate.

[0118] The temperature of the imprint mold can be controlled in the range of 100-200°C; properly heating the mold can improve the fluidity of the conductive paste and help it better fill the grooves.

[0119] Gap reservation: During the imprinting process, a certain gap is reserved by designing the mold or controlling the pressure. The gap can be within the range of 0.5-1μm to facilitate subsequent process operations.

[0120] Conductive paste drying

[0121] Drying temperature: The drying temperature should be between 100℃ and 200℃; the specific temperature selection depends on the composition of the conductive paste, especially the volatility of the solvent in the silver paste or copper paste.

[0122] It should be noted that silver paste is usually dried at 100-200℃ and sintered at 600-800℃.

[0123] Drying time: within this temperature range, the drying time is controlled at 0.5 minutes to 20 minutes. The specific time is adjusted according to the thickness of the slurry and the performance of the drying equipment. The time can be shortened at higher temperatures, while the drying time needs to be extended at lower temperatures.

[0124] Drying environment: Use a hot air circulation oven to ensure that the substrate and conductive paste are dried at a uniform temperature; of course, according to actual needs, they can be dried in an inert gas (such as nitrogen) environment to avoid oxidation or contamination.

[0125] S14, coating the second conductive paste in a preset shape, compounding the second conductive paste on the first conductive paste, and removing excess second conductive paste on the surface of the first substrate;

[0126] In this embodiment, preferably, S14, coating the second conductive paste in a preset shape, compounding the second conductive paste on the first conductive paste, and removing excess second conductive paste on the surface of the first substrate, includes:

[0127] The coated second conductive paste is closely contacted with the formed first conductive paste to form a firm composite layer;

[0128] By heating or applying pressure, the conductive pastes are fused with each other to ensure that there is no gap in the composite layer and a continuous conductive path is formed; wherein the heating temperature is 100-200°C and the duration is 5-10 minutes;

[0129] In this embodiment, preferably, S14, coating the second conductive paste in a preset shape, compounding the second conductive paste on the first conductive paste, and removing excess second conductive paste on the surface of the first substrate, further includes:

[0130] After removing the excess slurry, the conductive slurry needs to be initially dried at 100-200°C for 0.5-20 minutes to evaporate part of the solvent in the slurry and ensure that the slurry is initially solidified;

[0131] In order to completely solidify the conductive paste, a high-temperature sintering treatment is performed at a temperature of 500-1000°C and a curing time of 0.5-20 minutes. During this process, the internal structure of the conductive paste will be cross-linked and sintered, the conductive performance will be improved, and a stable electrode grid line will be formed.

[0132] Specifically, the second conductive paste is applied: the second conductive paste can be silver paste or other conductive materials, which must have excellent conductivity and good adhesion; the viscosity of the paste should be moderate to ensure that it can be evenly distributed and fill the grooves during the coating process.

[0133] Flat coating method: Pour the second conductive paste evenly on the first substrate, and then use a scraper or roller to apply pressure on the surface. The coating thickness should be controlled within the depth of the groove to ensure that the paste fills the preset shape.

[0134] Pressure compounding: After coating, a certain pressure can be applied to make the second conductive paste tightly bonded with the first conductive paste. The pressure value can be controlled within the range of 0.1MPa-0.3MPa to avoid over-compaction.

[0135] Drying and sintering: The second conductive paste needs to be dried or sintered. Usually the drying temperature is controlled at 100-200°C for 0.5-20 minutes to ensure that the solvent in the paste evaporates and is sintered into shape.

[0136] When the layers are combined, a layer-by-layer drying method is adopted, that is, the first conductive paste is preliminarily sintered, and then the second conductive paste is coated and compounded, and finally the whole is sintered.

[0137] Enhanced bonding strength: In order to increase the bonding strength between the two layers of conductive paste, a small amount of adhesive or interface treatment agent can be appropriately added to the paste to improve the adhesion between the two.

[0138] After coating and lamination, use a precision scraper or coating removal equipment to remove excess second conductive paste from the surface of the first substrate. Keep the scraper parallel to the surface during scraping to avoid damaging the formed groove structure.

[0139] The scraper should be made of moderately hard and wear-resistant materials, such as stainless steel or hard rubber, to avoid damaging the conductive paste. The scraper pressure should be kept uniform, generally controlled between 0.05MPa-0.1MPa, to ensure that the paste is only retained in the groove and the surface is smooth and flat.

[0140] Further, the first conductive paste is one of copper paste, chromium paste, tin paste, indium paste, nickel paste, titanium paste, and tantalum paste, and the second conductive paste is silver paste;

[0141] Wherein, the silver paste comprises a binder, and the binder is a phenolic resin or an epoxy resin.

[0142] Furthermore, the first substrate is made of a water-soluble polymer material, and the water-soluble polymer material is one of polyvinyl alcohol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, polyvinyl alcohol-polyacrylonitrile, polyvinyl pyrrolidone or polyethylene glycol.

[0143] It should be noted that polyvinyl alcohol is PVA in the present application.

[0144] Furthermore, the longitudinal cross-section of the groove of the electrode pattern is in the shape of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle or a polygon.

[0145] According to an embodiment of the present invention, preferably, before S11, providing a first substrate having a preset thickness and embossing a first substrate having an electrode pattern groove, the method further includes:

[0146] PVA films with a thickness of 30-125um were prepared by electrospinning or flat coating.

[0147] Specifically, electrospinning is a technology that uses electrostatic force to stretch a polymer solution into nano- or micron-sized fibers, which is used to prepare polymer material films.

[0148] By adopting the electrospinning method or the flat coating method, a PVA film with a thickness of 30-125um can be prepared, which can ensure good performance requirements and thus achieve a good matching effect.

[0149] According to an embodiment of the present invention, preferably, the width of the PVA film is 200-800 um, the elongation at break is 20-60%, the tensile strength is 5-20 MPa, and the Shore A hardness is greater than 70HS.

[0150] According to an embodiment of the present invention, preferably, the PVA content of the PVA film is greater than or equal to 90%, the average alcoholysis degree of PVA is 86-90%, and the plasticizer content is 1-3%.

[0151] By adopting the PVA film with the above parameters, the problem that the PVA film on the market cannot meet the silver / copper paste transfer function due to high softness, complex plasticizer composition, and high plasticizer ratio (10-20%) can be solved.

[0152] According to the transfer test of three PVA films prepared in the laboratory and purchased on the market, it is found that the PVA film used for silver / copper paste transfer needs to have the following physical and chemical properties:

[0153]

[0154]

[0155] It can be seen from the above table:

[0156] Different from coating PVA coating on high temperature resistant film, directly using PVA as a carrier can reduce the step of tearing the film after transfer, reduce the breakage of silicon wafers caused by tearing the film, and reduce a process. However, correspondingly, the hardness of the PVA film is required to be higher. In addition, because the thickness is greater than that of coating PVA coating on high temperature resistant film, the PVA in this scheme will take longer to dissolve in water at higher water temperature, about 2-5 minutes.

[0157] Of course, those skilled in the art should be familiar with the process when the flat-plate coating method is used for preparation.

[0158] This application controls the size and shape of the PVA transfer composite conductive grid lines through the parameters of the precision hot press (heating temperature, pressure, time, etc.) and different molds, thereby reducing the ohmic loss of the electrode grid lines. As a biodegradable and environmentally friendly material, PVA has low environmental harm. The PVA coating that is water-soluble at room temperature can greatly reduce the demolding cost. The method has a simple process, and the materials and equipment involved are economical and environmentally friendly, and the process cost is low. It is a new technology that can change the current printing pattern of silver electrode grid lines in photovoltaic cells. The contact part between the conductive paste and the silicon wafer determines its contact resistance, so the use of silver paste with better performance for the contact surface with the silicon wafer can ensure the conductive efficiency. The conductive part of the upper layer can be replaced by copper paste / copper paste to reduce costs. At present, only this nano-imprinting and transfer process can achieve this. And similarly, it can also be made into trapezoidal, rectangular and other shapes, such as Figure 4 As shown, it should be noted that the light grey is copper paste / carbon paste and the dark grey is silver paste.

[0159] The advantages of using high-precision embossing methods in this application include but are not limited to:

[0160] High resolution: The high-precision imprinting method can achieve pattern preparation at the micron level (within 10um), which has higher resolution and accuracy than traditional methods, helping to improve the performance and efficiency of photovoltaic cells.

[0161] High reproducibility: The nanoimprinting method has good reproducibility and can stably produce high-quality electrode patterns, ensuring the stability and reliability of photovoltaic cells.

[0162] Low cost: Compared with other micro-nano processing technologies, the nanoimprinting method is less expensive and suitable for large-area preparation, which helps to reduce production costs and improve production efficiency.

[0163] Versatility: The nanoimprinting method can realize the preparation of a variety of functional patterns, such as optical structures, surface-enhanced Raman scattering structures, etc., providing more possibilities for the performance optimization of photovoltaic cells.

[0164] Environmentally friendly and sustainable: The nanoimprint method usually does not require the use of organic solvents, has a lower environmental impact, meets the requirements of green manufacturing, and is conducive to sustainable development. By adding the advantages of the nanoimprint method, the innovation and practicality of the technical solution can be further highlighted, and the superiority and potential of the technical solution in the preparation of photovoltaic cell electrodes can be demonstrated.

[0165] From the above description, it can be seen that the present application achieves the following technical effects:

[0166] In an embodiment of the present application, a preparation process for a high-resolution composite silver / copper paste transfer film based on a PVA carrier and a nanoimprint process is adopted, by providing a first substrate with a preset thickness and an electrode pattern groove that is embossed; a first conductive paste that can at least fill the groove is applied to the embossed side of the first substrate, and excess first conductive paste on the surface of the first substrate is removed so that the surface of the groove and the surface of the first conductive paste are located on the same plane; a first mold is used to emboss the first conductive paste in the groove into a preset shape and a gap is reserved, and the overflowed first conductive paste is removed after the embossing; a second conductive paste is applied in the preset shape, the second conductive paste is compounded on the first conductive paste, and excess second conductive paste on the surface of the first substrate is removed to complete the preparation of the transfer film, thereby achieving the purpose of composite silver / copper paste, nanoimprinting and preparing the transfer film, thereby achieving the technical effect of reducing production costs and preparing high-resolution electrode patterns, thereby solving the problem of the traditional all-silver paste conductive path, although the conductive effect is good, the cost of silver paste is more expensive than copper paste, resulting in excessively high production costs; and the technical problem that the existing transfer film preparation process is relatively single.

[0167] like Figure 1-2 As shown, the present application also relates to a method for preparing a photovoltaic electrode grid line, comprising the following steps:

[0168] S1. Providing a transfer film prepared by a composite conductive paste transfer film preparation method;

[0169] S2, providing a second substrate, laminating the side of the first substrate having the conductive paste to the second substrate, and transferring the first conductive paste and the second conductive paste to the substrate by a embossing method with preset process parameters; wherein the embossing process parameters are: pressure of 5-20MPa, temperature of 80-180°C and time of 1-10min;

[0170] According to an embodiment of the present invention, preferably, S2, providing a second substrate, and laminating the first substrate with the side of the conductive paste on the second substrate, comprising:

[0171] The first conductive paste and the second conductive paste are hot-pressed and transferred to the second substrate by applying uniform pressure and heating and drying. At the same time, the first conductive paste and the second conductive paste are heated and dried so that they are tightly attached to the surface of the substrate without deformation; wherein the second substrate is one of a single crystal silicon substrate, a polycrystalline silicon substrate, a perovskite substrate, a glass substrate, and a plastic substrate.

[0172] The first conductive paste and the second conductive paste are hot-pressed and transferred onto the substrate by applying uniform pressure and heating and drying, and the first conductive paste and the second conductive paste are heated and dried at the same time so that they are closely attached to the surface of the substrate without deformation;

[0173] By applying uniform pressure to the side of the PVA film that is not coated with silver paste and heating and drying it, the photovoltaic paste can be transferred to the silicon wafer due to the adhesion between the photovoltaic paste and the silicon wafer, and the first conductive paste and the second conductive paste can fit tightly with the silicon wafer, thereby ensuring a good transfer effect and further ensuring the stability of the paste structure.

[0174] S3, removing the first substrate so that the first conductive paste and the second conductive paste remain on the second substrate;

[0175] According to an embodiment of the present invention, preferably, S3, removing the first substrate so that the first conductive paste and the second conductive paste remain on the second substrate, comprises:

[0176] The transferred silicon wafer is placed in 25-75°C water for cleaning, so that the PVA film dissolves and falls off, leaving the successfully transferred composite slurry pattern to form the basic structure of the photovoltaic electrode grid line.

[0177] The second substrate can be dissolved and removed, so that the composite slurry pattern is completely retained on the silicon wafer, thereby achieving a good dissolution and separation effect. The second substrate is a PVA film.

[0178] It should be noted that the water solubility of PVA can be changed by changing the alcoholysis degree of PVA, blending modification and other methods, so that it can be quickly dissolved at room temperature, and PVA is insoluble in gasoline, kerosene, vegetable oil, benzene, toluene, ethylene dichloride, carbon tetrachloride, acetone, ethyl acetate, methanol, ethylene glycol and other organic solvents. PVA is incompatible and non-reactive with the adhesive in the silver paste.

[0179] S4, sintering the first conductive paste and the second conductive paste on the second substrate to form photovoltaic composite paste electrode grid lines with a preset aspect ratio.

[0180] According to an embodiment of the present invention, preferably, S4, sintering the first conductive paste and the second conductive paste on the second substrate to form a photovoltaic composite paste electrode grid line with a preset aspect ratio, comprising:

[0181] The silicon wafer after transferring the first conductive paste and the second conductive paste is placed in a high-temperature furnace to sinter the composite paste; the sintering temperature is 500-800°C to ensure that the silver paste is completely sintered and forms a tight connection with the silicon wafer to generate high-precision photovoltaic electrode grid lines with a preset aspect ratio.

[0182] After high-temperature sintering, the first conductive paste and the second conductive paste can form silver paste electrode grid lines of required depth and width. Preferably, the size of the silver paste electrode grid lines is 10 um deep and 5 um wide.

[0183] The preparation process of the high-resolution composite silver / copper paste transfer film based on the PVA carrier of the present application has the following beneficial effects:

[0184] 1. High resolution: This method can achieve micron-scale or even nanoscale electrode patterns, which has higher resolution than traditional screen printing technology and helps improve the performance and efficiency of photovoltaic cells.

[0185] 2. Simple process: PVA carrier is used as the transfer carrier, the preparation process is relatively simple, the operation is convenient, and it is suitable for large-scale production.

[0186] 3. Low cost: PVA material cost is low, and this method can reduce waste generation, reduce material waste, and thus reduce production costs. At the same time, compared with the overall use of silver paste as a conductive path, the addition of copper paste can greatly reduce costs while ensuring conductive efficiency.

[0187] 4. High adhesion: PVA has no reactivity and weak adhesion with silver paste adhesives and solvents, and can effectively serve as an ideal carrier for transferring silver paste, which is conducive to the close fitting of silver paste and silicon wafer.

[0188] 5. Efficient production: Compared with screen printing technology, this method has higher production efficiency, can meet the needs of large-scale production, and improve production efficiency.

[0189] 6. Environmentally friendly and sustainable: PVA carrier is often dissolved after washing with warm water, which is environmentally friendly and sustainable, and helps to reduce the impact on the environment

[0190] 7. By mixing copper paste and silver paste, the purpose of reducing production costs while ensuring conductive efficiency is achieved.

[0191] 8. Using PVA as the transfer carrier, the effective transfer of copper paste and silver paste is achieved, ensuring the close fit between the copper / silver paste and the silicon wafer.

[0192] 9. The use of precision hot presses and molds enables high-resolution electrode pattern preparation, which helps improve the performance and efficiency of photovoltaic cells

[0193] 10. PVA has no reactivity and weak adhesion with copper paste and silver paste adhesives and solvents, and can serve as an ideal transfer carrier, which is conducive to the close bonding of copper / silver paste and silicon wafer.

[0194] 11. Through hot pressing and drying process steps, the copper / silver paste is accurately coated and sintered on the PVA carrier, ensuring the accuracy and stability of the electrode pattern.

[0195] The present application also relates to a photovoltaic cell, including the prepared photovoltaic electrode grid lines.

[0196] Further, it includes: a second substrate layer;

[0197] A second conductive paste layer is disposed on the second substrate layer at intervals along the length direction of the second substrate layer;

[0198] a first conductive paste layer connected to the second conductive paste layer in a thickness direction perpendicular to the second substrate layer;

[0199] The longitudinal cross-section of the first conductive paste layer is one of an isosceles triangle, an isosceles trapezoid, an ellipse, a hexagon, a right-angled trapezoid or a rectangle; the longitudinal cross-section of the second conductive paste layer is an isosceles trapezoid.

[0200] Furthermore, a passivation coating is provided between the first conductive paste layer and the second conductive paste layer. It is understood that a layer of passivation material, such as an aluminum oxide film or a transparent organic coating, is applied between the copper layer and the silver layer or on the silver layer to prevent moisture or corrosive substances in the environment from entering the interface between the two.

[0201] The photovoltaic cell using the photovoltaic electrode grid lines provided in this embodiment has the same basic principles and technical effects as those in the above embodiments. For matters not mentioned in this embodiment, please refer to the above corresponding contents.

[0202] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various equivalent transformations can be made to the technical scheme of the present invention, and these equivalent transformations all belong to the protection scope of the present invention.

Claims

1. A method for preparing a composite conductive paste transfer film, characterized in that: The following steps are involved: S11, providing a first substrate having a preset thickness and having an electrode pattern groove formed by embossing; S12, coating the first conductive paste on the embossing side of the first substrate so as to at least fill the groove, and removing the excess first conductive paste on the surface of the first substrate so that the groove and the surface of the first conductive paste are located on the same plane; S13, using a first mold to emboss the first conductive paste in the groove into a preset shape and leaving a gap, and removing the overflowed first conductive paste after embossing; S14, coating the second conductive paste in the preset shape, compounding the second conductive paste on the first conductive paste, and removing the excess second conductive paste on the surface of the first substrate to complete the preparation of the transfer film.

2. The method for preparing a composite conductive paste transfer film according to claim 1, characterized in that: S11, before providing a first substrate with a preset thickness and embossing a first substrate having an electrode pattern groove, the method further includes: PVA films with a thickness of 30-125um were prepared by electrospinning or flat coating.

3. The method for preparing a composite conductive paste transfer film according to claim 2, characterized in that: The PVA film has a width of 200-800 um, an elongation at break of 20-60%, a tensile strength of 5-20 MPa, and a Shore A hardness of greater than 70 HS.

4. The method for preparing a composite conductive paste transfer film according to claim 1, characterized in that: S11, providing a first substrate having a preset thickness and having an electrode pattern groove formed by embossing, comprising: The prepared PVA film is placed in the second mold by a precision hot press and hot embossing is performed in the temperature range of 150-200°C to form a micrometer-scale or even nanometer-scale electrode groove structure on the surface of the PVA film.

5. The method for preparing a composite conductive paste transfer film according to claim 4, characterized in that: The first mold and the second mold are one of a single crystal silicon substrate, a polycrystalline silicon substrate, a copper substrate, a nickel substrate, a copper-nickel alloy substrate, a nickel-iron alloy substrate, an iron-aluminum alloy substrate or an aluminum alloy substrate.

6. The method for preparing a composite conductive paste transfer film according to claim 4, characterized in that: The convex portion of the second mold is complementary in shape to the concave portion; Wherein, the shape of the mold is one of an isosceles triangle, an isosceles trapezoid, an ellipse, a hexagon, a right-angled trapezoid or a rectangle.

7. The method for preparing a composite conductive paste transfer film according to claim 1, characterized in that: S12, coating a first conductive paste that can at least fill the groove on the embossing side of the first substrate, and removing excess first conductive paste on the surface of the first substrate so that the groove and the surface of the first conductive paste are located on the same plane, comprising: The first conductive paste is evenly applied on the heat-pressed PVA film by a flat coating method, so that the first conductive paste completely fills the groove, and the excess first conductive paste is scraped off to ensure that the first conductive paste is completely filled and evenly distributed without deformation.

8. The method for preparing a composite conductive paste transfer film according to claim 1, characterized in that: S13, using a first mold to emboss the first conductive paste in the groove into a preset shape and leaving a gap, and removing the overflowed first conductive paste after embossing, including: A groove pattern with a height of 2-5 um, a width of 5 um and a reserved gap is pressed out using the first mold according to preset requirements, and the first conductive paste is dried at 100-200°C.

9. The method for preparing a composite conductive paste transfer film according to claim 1, characterized in that: S14, coating a second conductive paste in a preset shape, compounding the second conductive paste on the first conductive paste, and removing excess second conductive paste on the surface of the first substrate, including: The coated second conductive paste is closely contacted with the formed first conductive paste to form a firm composite layer; By heating or applying pressure, the conductive pastes are fused together to ensure that there are no gaps in the composite layer and form a continuous conductive path.

10. The method for preparing a composite conductive paste transfer film according to claim 1, characterized in that: S14, coating the second conductive paste in a preset shape, compounding the second conductive paste on the first conductive paste, and removing excess second conductive paste on the surface of the first substrate, further comprising: After removing the excess slurry, the conductive slurry needs to be initially dried at 80-100°C for 10-20 minutes to evaporate part of the solvent in the slurry and ensure that the slurry is initially solidified; In order to completely cure the conductive paste, high-temperature curing treatment is performed again at a temperature of 150-200°C and a curing time of 30-60 minutes. During this process, the internal structure of the conductive paste will be cross-linked and sintered, the conductive performance will be improved, and a stable electrode grid line will be formed.

11. The method for preparing a composite conductive paste transfer film according to claim 1, characterized in that: The first conductive paste is one of copper paste, chromium paste, tin paste, indium paste, nickel paste, titanium paste and tantalum paste, and the second conductive paste is silver paste; Wherein, the silver paste comprises a binder, and the binder is a phenolic resin or an epoxy resin.

12. The method for preparing a composite conductive paste transfer film according to claim 1, characterized in that: The first substrate is made of a water-soluble polymer material, and the water-soluble polymer material is one of polyvinyl alcohol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, polyvinyl alcohol-polyacrylonitrile, polyvinyl pyrrolidone or polyethylene glycol.

13. The method for preparing a composite conductive paste transfer film according to claim 1, characterized in that: The longitudinal cross-section shape of the groove of the electrode pattern is one of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle or a polygon.

14. A method for preparing a photovoltaic electrode grid line, characterized in that: The following steps are involved: S1. Provide a transfer film prepared by the method for preparing a composite conductive paste transfer film according to any one of claims 1 to 13; S2, providing a second substrate, laminating the side of the first substrate having the conductive paste to the second substrate, and transferring the first conductive paste and the second conductive paste to the substrate by a embossing method with preset process parameters; wherein the embossing process parameters are: pressure of 5-20MPa, temperature of 80-180°C and time of 1-10min; S3, removing the first substrate so that the first conductive paste and the second conductive paste remain on the second substrate; S4, sintering the first conductive paste and the second conductive paste on the second substrate to form photovoltaic composite paste electrode grid lines with a preset aspect ratio.

15. The method for preparing photovoltaic electrode grid lines according to claim 14, characterized in that: S2, providing a second substrate, and laminating the first substrate with the side of the conductive paste on the second substrate, comprising: The first conductive paste and the second conductive paste are hot-pressed and transferred to the second substrate by applying uniform pressure and heating and drying. At the same time, the first conductive paste and the second conductive paste are heated and dried so that they are tightly attached to the surface of the substrate without deformation; wherein the second substrate is one of a single crystal silicon substrate, a polycrystalline silicon substrate, a perovskite substrate, a glass substrate, and a plastic substrate.

16. The method for preparing photovoltaic electrode grid lines according to claim 14, characterized in that: S3, removing the first substrate so that the first conductive paste and the second conductive paste remain on the second substrate, comprising: The transferred silicon wafer is placed in 25-75°C water for cleaning, so that the PVA film dissolves and falls off, leaving the successfully transferred composite slurry pattern to form the basic structure of the photovoltaic electrode grid line.

17. The method for preparing photovoltaic electrode grid lines according to claim 14, characterized in that: S4, sintering the first conductive paste and the second conductive paste on the second substrate to form a photovoltaic composite paste electrode grid line with a preset aspect ratio, including: The silicon wafer after transferring the first conductive paste and the second conductive paste is placed in a high-temperature furnace to sinter the composite paste; the sintering temperature is 500-800°C to ensure that the silver paste is completely sintered and forms a tight connection with the silicon wafer to generate high-precision photovoltaic electrode grid lines with a preset aspect ratio.

18. A photovoltaic cell, characterized in that The invention comprises a photovoltaic electrode grid line prepared by the preparation method according to any one of claims 14 to 17.

19. The photovoltaic cell according to claim 18, characterized in that: include: a second substrate layer; A second conductive paste layer is disposed on the second substrate layer at intervals along the length direction of the second substrate layer; and a first conductive paste layer connected to the second conductive paste layer in a thickness direction perpendicular to the second substrate layer; The longitudinal cross-section of the first conductive paste layer is one of an isosceles triangle, an isosceles trapezoid, an ellipse, a hexagon, a right-angled trapezoid or a rectangle; the longitudinal cross-section of the second conductive paste layer is an isosceles trapezoid.

20. The photovoltaic cell according to claim 19, characterized in that: A passivation coating is disposed between the first conductive paste layer and the second conductive paste layer.

Citation Information

Patent Citations

  • Protruding electrode for connecting electronic component, electronic component mounted body using such electrode and methods for manufacturing such electrode and electronic component mounted body

    CN101156238A

  • Preparation method of patterned metal transparent conductive film

    CN104835555A

  • Metal grid film and preparation method thereof

    CN112566365A

  • Electrode flattening treatment method and electrode manufactured by adopting same

    CN116845133A

  • Circuit substrate of touch device

    CN203858605U

Cited By

  • Shape memory transfer printing film, preparation method thereof and battery piece grid line preparation method

    CN120504943A

  • A photovoltaic electrode composite grid line and a preparation method and application thereof

    CN122971043A

  • Solar cell and preparation method therefor

    WO2026178967A1